Single-shot switching in Tb/Co-multilayer based nanoscale magnetic tunnel junctions - Mondal, Sucheta; Polley, Debanjan; Pattabi, Akshay; Chatterjee, Jyotirmoy; Salomoni, David; Aviles Felix, Luis Steven; Olivier, Aurélien; Rubio Roy, Miguel; Diény, Bernard; Prejbeanu, Liliana Daniela Buda; Sousa, Ricardo; Prejbeanu, Ioan Lucian; et al. (Elsevier Science, 2023)
Fil: Mondal, Sucheta. University of California; Estados Unidos